Molecular differences in the microsatellite stable phenotype between left‐sided and right‐sided colorectal cancer. Issue 11 (19th September 2016) - Takahashi, Yayoi; Sugai, Tamotsu; Habano, Wataru; Ishida, Kazuyuki; Eizuka, Makoto; Otsuka, Koki; Sasaki, Akira; Takayuki Matsumoto; Morikawa, Takanori; Unno, Michiaki; Suzuki, Hiromu
Abstract : Differences in the pathogenesis of microsatellite stable (MSS) sporadic colorectal cancers (CRCs) between left‐sided CRC (LC) and right‐sided CRC (RC) have not been clarified. To identify pathogenesis‐related genomic differences between MSS CRCs within the two locations, we performed a comprehensive molecular analysis using crypt isolation with samples from 92 sporadic CRCs. Microsatellite instability (MSI; high and low/negative) and DNA methylation status (low methylation epigenome; intermediate methylation epigenome [IME] or high methylation epigenome [HME]) were determined using polymerase chain reaction (PCR) microsatellite analysis and PCR‐bisulfite pyrosequencing, respectively. Additionally, mutations in the TP53, KRAS, BRAF and PIK3CA genes were examined using PCR‐bisulfite pyrosequencing (for KRAS and BRAF mutations) or PCR‐single conformation polymorphism (for TP53 and PIK3CA mutations), followed by sequencing of aberrant bands. Finally, a genome‐wide study using a copy number alteration (CNA)‐targeted single nucleotide polymorphism array was performed. Ninety‐two CRCs were classified into 71 MSS and 21 MSI phenotypes. We examined 71 CRCs with the MSS phenotype (LC, 56; RC, 15). Mutations in KRAS were associated with RC with the MSS phenotype, whereas mutations in TP53 were more frequently found in LC with the MSS phenotype. There were significant differences in the frequencies of KRAS and TP53 mutations in the IME between LC and RC with the MSS phenotype. Although CNA gains were associated with LC with the MSS phenotype, CNA losses were not major alterations associated with the MSS phenotype. These findings suggested that the molecular pathogenesis of the MSS phenotype in LC was different from that in RC. Abstract : What's new? The classification of colorectal cancer (CRC) based on tumor location is simple, comprehensive, and consistent with recent attempts to characterize tumors by pathological and molecular features. Differences in the pathogenesis of microsatellite stable (MSS) sporadic CRCs between left‐sided CRC (LC) and right‐sided CRC (RC) have however not been clarified. Here, the authors found that TP53 mutations are closely associated with the development of LC whereas RC is characterized by KRAS mutations. Using an integrated genome‐wide analysis, they also show significant differences in copy number alterations. The findings suggest a different molecular pathogenesis of the MSS phenotype between LC and RC.